Pneumococcal septic arthritis in adults: clinical analysis and review. Issue 1 (February 2014) - Belkhir, L.; Rodriguez-Villalobos, H.; Vandercam, B.; Marot, J. C.; Cornu, O.; Lambert, M.; Yombi, J. C.
Abstract : Background: Septic arthritis (SA) is a rheumatological emergency that can lead to rapid joint destruction and irreversible loss of function. The most common pathogen causing SA is Staphylococcus aureus which is responsible for 37–65% of cases. Streptococcus pneumoniae is traditionally described as an uncommon cause of SA of a native joint. The objective of our study was to analyse clinical characteristics, treatment, and outcome of all cases of pneumococcal septic arthritis treated in our institution, and to compare them with other series published in the literature. Materials and methods: We conducted a retrospective study of pneumococcal SA identified among all cases of SA diagnosed in a teaching hospital of one thousand beds between 2004 and 2009. Diagnosis was based on culture of joint liquid or by the presence of pneumococcal bacteraemia and purulent (more than 50 000/mm 3 white blood cells with more than 90% neutrophils) joint fluid aspiration. Results: Among 266 cases of SA, nine patients (3·3%) were diagnosed as having pneumococcal SA. The median age was 75 years. The main affected joint was the knee (7/9). No patient had more than one joint involved. Four patients suffered from concomitant pneumonia. Joint culture and blood cultures were positive in 7/9 and 5/9, respectively. Median (range) length of stay was 18 days (3–47 days). One patient with associated pneumococcal bacteraemia died 19 days after admission. Seven patients recovered completely. Conclusions: Streptococcus pneumoniae is now being increasingly recognized as a common agent of SA. This organism is frequently associated with pneumococcal pneumonia or bacteraemia, particularly in patients with advanced age and comorbidities. Direct inoculation of joint fluid into blood culture medium BACTEC system increases the probability of microbiological diagnosis. The prognosis is usually favourable if the disease is promptly recognized and treated (antibiotic therapy combined with joint drainage).